Cognitive functioning in the general population: Factor structure and association with mental disorders—The neuropsychological test battery of the mental health module of the German Health Interview and Examination Survey for Adults (DEGS1‐MH). Issue 1 (6th November 2017) - Wagner, Michael; Wolfsgruber, Steffen; Gaertner, Beate; Kleineidam, Luca; Buttery, Amanda K.; Jacobi, Frank; Van der Elst, Wim; Jolles, Jelle; Hapke, Ulfert; Wittchen, Hans‐Ulrich; Maier, Wolfgang; Busch, Markus A.
Abstract: The objective of this study is to obtain population level data about cognitive functions and their association with mental disorders. We here report factor analytic and psychometric findings of a neuropsychological test battery and examine the association of current and past mental disorders with cognitive function in a large nationwide population‐based sample of 18‐ to 79‐year‐old adults in Germany ( n  = 3, 667) participating in the mental health module of the German Health Interview and Examination Survey for Adults 2008–2011. Confirmatory factor analysis confirmed verbal memory and executive function factors. Older age was strongly associated with lower verbal memory and executive function and with higher vocabulary scores. After adjustment for age, sex, and education, rather modest decrements were found for verbal memory (β = −.118, p  = .002) and executive functions (β = −.191, p  < .001) in participants with any current mental disorder ( n  = 442) compared to those without ( n  = 3, 201). Small decrements in memory (β = −.064, p  = .031) and executive function (β = −.111, p  < .001) were found in participants with any mental disorder in the last 12 months but not in those with past (fully or partially remitted) mental disorders, compared to participants without a history of mental disorder. More fine‐grained analyses of these data will investigate the complex interplay between cognition, health behaviors, and specific mental and somatic diseases.